Sustainability of Barangay Micro Business Enterprises (BMBEs) in Banna, Ilocos Norte - Bibeth L. Macatumbas-Corpuz; Nelson C. Bool (Research Synergy Foundation, 2021)
This study determined the sustainability of Barangay Micro Business Enterprises (BMBEs) in Banna, Ilocos Norte. The research design for this study was descriptive-correlational. Data were gathered using a self-constructed questionnaire, which has been pre-tested to 30 other microenterprises and validated using Cronbach alpha. The participants were the owners of the 60 registered BMBEs in Banna, Ilocos Norte. This study was conducted from July to August 2020. The study found out that the BMBEs sometimes practice financial management, marketing, and manufacturing or trading practices. They have never availed of the different benefits and incentives that are provided in the BMBE Law. They sometimes experience problems that affect their operations. The BMBEs have moderate economic sustainability but high social and environmental sustainability. The business practices have a significant positive relationship with the BMBEs sustainability, while the benefits and incentives have a significant negative relationship with the BMBEs sustainability. However, the problems they encounter has no significant relationship with sustainability. The BMBEs are vulnerable, but by following different business practices, they manage to become sustainable despite their failure to avail the different benefits and incentives provided in the BMBE Law and the problems that they encounter in their business operations.